An artificial hybrid interphase for an ultrahigh-rate and practical lithium metal anode. Issue 7 (22nd June 2021) - Hu, Anjun; Chen, Wei; Du, Xinchuan; Hu, Yin; Lei, Tianyu; Wang, Hongbo; Xue, Lanxin; Li, Yaoyao; Sun, He; Yan, Yichao; Long, Jianping; Shu, Chaozhu; et al.
Abstract : The present work theoretically and experimentally provides an insight into the internal mechanism of Li + transport within an artificial hybrid SEI layer consisting of lithium-antimony (Li3 Sb) alloy and lithium fluoride (LiF). Abstract : The solid electrolyte interphase (SEI) layer is pivotal for stable lithium (Li) metal batteries especially under a high rate. However, the mechanism of Li + transport through the SEI has not been clearly elucidated to build robust Li anodes for practical Li metal batteries. Herein, an artificial hybrid SEI layer consisting of lithium-antimony (Li3 Sb) alloy and lithium fluoride (LiF) is constructed to explore the ion diffusion behaviors within the SEI. As evidenced theoretically and experimentally, Li3 Sb is identified as a superionic conductor for Li + transport and as an interfacial stabilizer for the SEI layer while the LiF component with superior electron-blocking capability reduces the electron tunneling from the Li anode into the SEI, resulting in uniform dendrite-free Li deposition at the SEI/Li interface and stable Li plating/stripping behaviors at an ultrahigh rate of 20 mA cm −2 . A practical 325.28 W h kg −1 pouch cell is well demonstrated under a high sulfur loading of 6 mg cm −2 and a low electrolyte/sulfur ratio of 3 μl mg −1 . This work uncovers the internal mechanism of Li + transport within the SEI component, and provides an avenue to stabilize the Li anode under practical high-rate conditions.